2016
DOI: 10.4314/evj.v20i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Major reproductive disorders on Jersey breed dairy cattle at Adea Berga dairy farm, West Shewa Zone, Oromia Region, Ethiopia

Abstract: Reproductive efficiency of dairy cows is influenced by different factors including gene, season, age, production system, nutrition, management, environment and disease. This study was conducted with the objectives of determining the prevalence of reproductive disorders and evaluates reproductive performances of Jersey dairy cattle maintained at Adea berga dairy farm. The retrospective and longitudinal studies were employed through document revision; clinical and laboratory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…These results indicated that cattle abortion is a common reproductive disorder with different prevalences. 8,12,20 The highest prevalence of abortion (28.9%) was observed by Siyoum et al 21 in west Shewa. On the other hand, Gizaw et al 22 reported a relatively lower abortion prevalence (2.2%) in central Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…These results indicated that cattle abortion is a common reproductive disorder with different prevalences. 8,12,20 The highest prevalence of abortion (28.9%) was observed by Siyoum et al 21 in west Shewa. On the other hand, Gizaw et al 22 reported a relatively lower abortion prevalence (2.2%) in central Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…A study conducted by Regassa et al (2016) on major factors influencing the reproductive performance of dairy farms in Mekelle city, Tigray reported 13.3% (n=798) prevalence of abortion. Recent reports from Adea Berga (Siyoum et al, 2016), Horro Gudru (Wagari and Shiferaw, 2016) and Wolaita Sodo town (Enda and Moges, 2016) indicated that the prevalence of 28.9 (n=97), 4.4 (n=402) and 4.8% (n=104) of abortion was recorded in cattle, respectively.…”
Section: Status Of Abortion In Dairy Cows In Ethiopiamentioning
confidence: 99%
“…The prevalence rate of abortion varies in different production system and from place to place. Prevalence rate of abortion in Ethiopia range from 2.2 to 28.9% (Table 3) (Gizaw et al, 2007;Siyoum et al, 2016). This difference in prevalence rate may be due to variation in cattle breed and husbandry management system.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…The mean AFS, AFC and CI were lower than previous reports. A 26 years retrospective analysis made by Yalew et al (Yalew et al 2011), a reproductive constraint in crossbred dairy cows under four different production systems in the central highlands of Ethiopia by Shiferaw et al (Shiferaw et al 2003), reproductive performances of Jersey dairy cattle maintained at Adeaberga dairy farm by Siyoum et al (Siyoum et al 2016) showed the mean AFS, AFC and CI to be 26-29 M, 35-41M and 15-18M, respectively. The difference might be attributed to the impact of training and large-scale dairy technology demonstration performed in the area and the interventions of various stakeholders on dairy feeding and nutrition, management and health, to better the reproductive and productive performance.…”
Section: Reproductive Performance Of Selected Cowsmentioning
confidence: 99%